The Association of Childhood Sexual Abuse With Non-Paraphilic and Paraphilic Sexual Behaviors Among Adolescents Who Have Sexually Offended. Issue 9 (21st November 2020) - Leroux, Elisabeth J.; Clow, Kari-Ann; Motayne, Greg; Seto, Michael C.
ABSTRACT: A history of childhood sexual victimization (CSV) is one of the most commonly examined factors in research on male adolescent sexual offending. Although CSV has been extensively researched in relation to the onset and maintenance of adolescent sexual offending, few studies have investigated the association of CSV with domains of adolescent sexuality outside of sexual offending. Understanding how CSV may be associated with the non-paraphilic, and paraphilic, sexual behaviors of adolescent males who commit sexual offenses has important implications for promoting healthy sexuality among this population. In a sample of 162 male adolescents ( M age = 15.2 years, SD  = 1.3) adjudicated for a sexual offense, we tested the association of CSV with a range of non-paraphilic (e.g., age of first consensual sex) and paraphilic (e.g., use of paraphilic pornography) sexual behavior variables. The results indicated CSV was associated with greater engagement in risky non-paraphilic sexual behaviors, as well as paraphilic sexual behaviors. CSV was also associated with specific offense characteristics, replicating previous research findings. The current study is a first step toward understanding the broader sexual context of adolescents who commit sexual offenses.